Comparison of Flow Solutions for Naturally Fractured Reservoirs Using Complex Analysis Methods (CAM) and Embedded Discrete Fracture Models (EDFM): Fundamental Design Differences and Improved Scaling Method. (13th October 2020) - Khanal, Aaditya; Weijermars, Ruud
Abstract : The present study compares flow paths in reservoirs with natural fractures, solved with Complex Analysis Methods (CAM), to those solved with Embedded Discrete Fracture Models (EDFM). One aim is to define scaling rules for the strength (flux) of the discrete natural fractures used in CAM models, which was previously theoretically defined based on the expected flow distortion. A major hurdle for quantitative benchmarks of CAM with EDFM results is that each of the two methods accounts for natural fractures with different assumptions and input parameters. For example, EDFM scales the permeability of the natural fractures based on a cubic equation, while CAM uses a flux strength. The results from CAM and EDFM are used to scale the flux strength of the natural fractures and improve the equivalent permeability contrast estimation for CAM. The permeability contrast for CAM is calculated from the ratio of the enhanced velocity inside natural fractures to the unperturbed matrix fluid velocity. A significant advantage of flow and pressure models based on CAM is the high resolution without complex gridding. Particle tracking results are presented for fractures with different hydraulic conductivity ranging from highly permeable to impervious.